Preventive remediation methods minimize soil pollution - Sarwoko Mangkoedihardjo; Harida Samudro (Institute of Advanced Engineering and Science, 2023)
Soil quality is rich in various substances, as well as a rich variety of uses for life, which leads to the potential for pollution. Once soils are polluted, remediation is mitigative and must be carried out, which has been the focus of many studies so far. However, preventive remediation is the focus of the novelty of this study, which aims to prepare predictive methods. This is a literature review of various studies over the last ten years, which are related to soil quality indicators through the respiration process. Based on the soil microbial respiration process platform, which contains various substances, the results of this study found three preventive remediation methods, namely indicators of substance reactants, gas products, and toxicity to microbes. The three methods simply require measuring the parameters of biochemical oxygen demand, and chemical oxygen demand, in addition to specific measurements of carbon dioxide and microbial enumeration. The advantage of the preventive remediation method is the application of soil response indicators to various types and amounts of contaminants. The implementation of preventive remediation is prior to building infrastructure, which is able to predict changes in soil quality through monitoring, thereby minimizing the potential for mitigative remediation.